Acute toxicity of live and decomposing green alga Ulva （Enteromorpha） prolifera to abalone Haliotis discus hannai - 王超 于仁成 周名江 (中国海洋湖沼学报：英文版, 2011)
From 2007 to 2009, large-scale blooms of green algae （the so-called ＂green tides＂） occurred every summer in the Yellow Sea, China. In June 2008, huge amounts of floating green algae accumulated along the coast of Qingdao and led to mass mortality of cultured abalone and sea cucumber. However, the mechanism for the mass mortality of cultured animals remains undetermined. This study examined the toxic effects of Ulva （Enteromorpha） prolifera, the causative species of green tides in the Yellow Sea during the last three years. The acute toxicity of fresh culture medium and decomposing algal effluent of U. prolifera to the cultured abalone Haliotis discus hannai were tested. It was found that both fresh culture medium and decomposing algal effluent had toxic effects to abalone, and decomposing algal effluent was more toxic than fresh culture medium. The acute toxicity of decomposing algal effluent could be attributed to the ammonia and sulfide presented in the effluent, as well as the hypoxia caused by the decomposition process.